Strategi Komunikasi Media Sosial untuk Mendorong Partisipasi Masyarakat pada Website Sajiwa Foundation - Rachilia Ramadhini Irmansyah; Anindita Lintangdesi Afriani (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
In this digital age, social media has become an important platform in connecting organizations with the community and encouraging active participation and helping to increase the organization’s social impact. One such organization’s is Sajiwa Foundation, a-non profit organization that focuses on educating and supporting the utilization needs of people in need. The purpose of this study is to provide insight into how non-profit organization can use social media communication strategies effectively to encourage community participation on the Sajiwa Foundation website platform Sajiwa Foundation this research aims to identify the various strategies used by Sajiwa Foundation to motivate people to actively participate in campaigns and programs offered through their website. This research used a qualitative approach by conducting a content analysis of Sajiwa Foundation’s social media accounts and involved interviews with Sajiwa Foundation team members. From analysis, the importance of an appropriate social media communication strategy in encouraging community participation in the context of non-profit organization was found to have several key elements. First, content should be veried and relevant, covering information and inspiring stories and the development of the organization. Second, attractive visuals can increase user interaction. Third, active interaction with the online community through comment, direct messages and calls to action helps build deeper relationships with the audience. This provides valuable insights for similar organizations looking to maximize their impact through leveraging social media as a powerful communication tool towards the wider community.